Voltammetric and spectroelectrochemical properties of titanylphthalocyanines bearing catecholato and naphthalenediolato moieties - KOCA, ATIF (ELSEVIER SCIENCE SA, 2008)
Detailed electrochemical characterization of catecholato-octakis(2-dimethylaminoethylsulfanyl phthalocyaninato) titanium(IV) and (2,3-naphthalenediolato)-octa-(2-dimethylaminoethylsulfanylphthalocyaninato) titanium(IV) derivatives has been carried out by cyclic voltammetry, differential pulse voltammetry, double potential step coulometry, controlled potential coulometry and spectroelectrochemical measurements. Cyclic and differential pulse voltammograms of the complexes are similar with two metal-based and two ligand-based reduction and two ligand-based oxidation couples. Capping of TiO core of octakis(2-dimethylaminoethylsulfanyl)phthalocyaninato oxotitanium(IV) with catecholato and naphthalenediolato changed the redox mechanism of the complexes. (2,3-naphthalenediolato)octa-(2-dimethylaminoethylsulfanylphthalocyaninato) titanium(IV) derivative is dimetallised during the negative potential sweeps. Spectroelectrochemical measurements confirm the metal- and ligand-based assignments of the redox couples. Distinctive voltammetric and spectroscopic changes during the titration with soft metal ions, Ag+ and Pd2+, shows the metal sensing and coordinating properties of the complexes. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: spectroelectrochemistry; catechol; naphthalenediolato; cyclic voltammetry; oxotitanium(IV); phthalocyanines; ELECTROCHEMICAL CHARACTERIZATION; SUBSTITUTED COBALT; PHTHALOCYANINES; POLYMERIZATION; COMPLEXES; MANGANESE